The Practice of Islamic Funeral Rites for Students at Sultan Hasanuddin Islamic Boarding School in Gowa Regency - Muhammadong; Muthmainnah, Sitti; Nurhilaliyah, Nurhilaliyah; Khaerunnisa, Khaerunnisa (Lumbung Pare Cendekia, 2025)
Death is an undeniable axiom for human beings, as it is a decree set by Allah that must be followed. It is an obligation for the living to fulfill the Islamic rites for the deceased, meaning that the dead must be treated with respect and dignity, just as one would treat the living. The duties of the living toward the deceased include washing the body, shrouding it, performing the funeral prayer, and burying it. The community service program (PKM) conducted at Sultan Hasanuddin Islamic Boarding School in Gowa Regency was a practical training on funeral rites, aimed at equipping the students (santri) with knowledge and skills in handling the deceased. This activity was carried out to enrich the students' religious insight, enabling them to properly fulfill the communal obligation (fardhu kifayah) as instructed in Islamic teachings. The methods used included discussions, hands-on practice, Q&A sessions, demonstrations, and evaluations of the outcomes of the program. The results showed that the students at Sultan Hasanuddin Islamic Boarding School in Gowa Regency were able to understand and perform the funeral rites well, with the potential to implement this knowledge within their communities.